Sensory Analysis Of Dry Noodles Of Buni Fruit Extract (Antidesma bunius (L) Spreng) - shofiya Nadia Kafi; Ulfa Maulida Farid (TAPE : Jurnal Teknologi Hasil Pertanian, 2025)
Buni is a small fruit arranged in a chain-like structure on its stem. The purpose of this study was to determine the Sensory Analysis of Dry Noodles with Buni Fruit Extract (Antidesma bunius (L) Spreng). The method used in this study used sensory analysis with a hedonic scale. Data analysis used was One Way Anova. The experimental design used was RAL with buni fruit extract at P1 = 75% wheat flour with 25 ml of buni fruit extract, P2 = 75% wheat flour with 50 ml of buni fruit extract, P3 = 75% wheat flour with 75 ml of buni fruit extract, P4 = 75% wheat flour with 100 ml of buni fruit extract. The results of the sensory analysis of dry noodles including color, aroma, taste and texture carried out on 30 panelists, on average the panelists liked dry noodles with 100 ml of buni fruit extract (P4). Based on the results of the one-way ANOVA test on each aspect, the color aspect was 0.03 <0.05, the aroma aspect was 0.03 <0.05, the taste aspect was 0.04 <0.05, and the texture aspect was 0.04 <0.05, which means there is a significant influence on the four aspects of sensory analysis.